'TAKING THE HEAT': FRONT-LINE EXPERIENCES OF DISCHARGE PLANNING - Lawson, Lori A. (My University, 2013)
With government pressure to cut healthcare costs, the hospital sector in Ontario has directed increased attention to moving patients out of the hospital as soon as they are deemed not to require acute care. Discharge planning has become a highly measured and managed process facilitated by social workers and Community Care Case Managers. The purpose of this thesis is to look at the experiences of hospital social workers and CCAC case managers and the common (and distinct) ways they experience their discharge planning roles and responsibilities. Information was obtained from two focus groups: one with hospital social workers and the other, with hospital CCAC case managers. Themes from the focus group of social workers emerged that illustrated the ‘heat’ in discharge planning and the implications this pressure had on patients and families, and the role of social work. Two dominant sources of pressure on discharge planning were the provincial focus on reducing wait times and organizational performance markers related to patients’ length of stay. Social workers voiced their concerns about government rhetoric and the inadequacies in community resources for ‘aging at home’, constrained choices and coerced caregiving that had implications for patients and families. CCAC case managers experienced similar pressures to discharge patients quickly while wanting more time to spend with them so that they could arrange the most appropriate services and care plans. CCAC case managers described the unique experience of working in an organization that is not their employer and having to facilitate ‘their’ discharge planning policies. This study looked at the inter-professional relations between social workers and CCAC case managers and how professional identity impacts the role of discharge planning. Social workers associated a certain “character” as needed to stand up against a system that is not always working in the best interests of patients and families.
Keywords: social work; discharge planning; CCAC; case managers;home care; Social Work; Social Work